The gyrotron startup scenario in the single mode time dependent approach - Nowak, Kacper; Plinski, Edward Franciszek; Wieckowski, Tadeusz; Dumbrajs, Olgierd (Mathematical Modelling and Analysis, 2019)
The paper explains how to solve the Gyrotron equation system in the Single Mode Time Dependent Approach. In particular, we point out problems encountered when solving these well-known equations. The starting current estimation approach a using time model is suggested. The solution has been implemented in the Matlab code, which is attached to the article.